Does game-based training replicate match inside-50 entries in elite Australian Rules football? - Wallace, O.; Vickery, W.; Bruce, L. (International Journal of Sports Science & Coaching, 2024)
The purpose of this research was to determine if the training design of an elite Australian Rules football team replicated match conditions for inside-50 entries. Notational analyses of one professional Australian Rules football club's training and match footage were conducted for every disposal that entered the inside-50 during either game-based training or matches. Analysed variables included how the ball was received, time in possession and location. Statistical analyses were undertaken using Mann-Whitney tests, a multivariate analysis of variance and a decision tree analysis. Significant differences were identified between game-based training and competition matches for 34 of the 54 inside-50 entry variables. Of these 34 variables, 10 showed a strong effect between session types. When examining the efficiency of inside-50 entries, only effective disposals produced a significant difference between training and matches, with no differences for neutral and ineffective disposals. The session type, how the ball was received, decision (e.g., kick vs. handball) and pressure acts were the most important contributors to effective inside-50 entry disposal efficiency. The results suggest this professional Australian Rules team does not participate in training sessions that reflect inside-50 match conditions. This study may provide a framework for elite Australian Rules teams on which to structure their inside-50 training.